Caracterización de los estudiantes de las especializaciones clínicas de la facultad de odontología de la Universidad de Antioquia, semestre 2004-1 (2007)
ABSTRACT: Students characterization is a procedure in the generation of information because it allows to diagnose, evaluate and provide feedback for curricular planning and organization. Methods: the purpose of this descriptive transversal study was to identify the demographic, socioeconomic, academic and professional characteristics, as well as other extracurricular activities of postgraduate students at the School of dentistry of the Universidad de Antioquia enrolled during the first semester 2004. The sample consisted of 48 students who answered a survey with open and closed questions, the data was processed by means of EPI-INFO program. Results and conclusions: the results showed that the majority of students are single women with a range of ages between the 28 and 30 years; more that half of them work between 6 and 10 hours a week and earn between 1 and 2 minimum wage monthly salaries. They mostly work in the clinical areas without affecting their academic performance because of it, inversely; their work is not hindered by their academics obligations. The information presented here could useful for curricular design and future planning as well as for accreditation processes of postgraduate programs.